The Relationship between Shift Work and Occupational Fatigue on Nurses Working on the Pediatrics and Internal Wards of Muhammadiyah Palembang Hospital - Ardi Artanto; Liza Chairani; Melisa Nopa Belia; Ahmad Ghiffari (Britain International of Exact Sciences (BIoEx) Journal, 2021)
Shift work is a method of allocating work time to different workgroups. Fatigue is defined as an abnormal sensation of tiredness, sluggishness, or a lack of desire to engage in activities, which results in stress, depression, or other negative emotions. In order to satisfy patients within 24 hours, hospitals must organize nurses by shift. The goal of this study at Muhammadiyah Palembang Hospital was to see if there was a link between shift work and fatigue in pediatric and internal ward nurses. This cross-sectional and analytic study entailed 26 respondents from the total sampling method used. In this study, those who worked shifts included those who worked in the morning (12 respondents (46.2 %), evening (8 respondents (30.8%), and night (6 respondents (23.1 %). Fatigue has been linked to 38% of RSMP's overworked pediatric ward nurses and interna, with a p-value of 0.029. The hospital should provide rest periods for nurses, especially those who work the last shift because they must adapt during the night.